Religiosity and quality of life among breast cancer patients: an integrative literature review - Rosliana Dewi; Santha Letchmi Panduragan; Nur Syazana Umar; Ghulam Ahmad (Intelektual Pustaka Media Utama, 2022)
This paper examines recent data on the relationship between religiosity and quality of life. It also identifies emerging issues arising from the link between religion and quality of life. An integrative research review design implemented to review the existing articles on religiosity and quality of life. Search was conducted between January and February, 2021 in three online databases (PubMed, PsycINFO, and ScienceDirect) using MeSH keywords such as 'religion' or 'religiosity', 'quality of life' and 'breast cancer,' Initial search resulted on 264 articles, however only nine articles met eligibility criteria for review. The seven of the studies employed a cross-sectional design and two studies implemented prospective design. The definition of religiosity and quality of life were varying in included study. Most of studies reported positive correlation and direct effect between religiosity and quality of life. Two studies reported no association between religiosity and quality of life. Two studies investigate the role of religiosity as moderating variabel; religiosity mediated relationship between posttraumatic growth and quality. A greater emphasis on the importance of religiosity in healthcare services and partnerships with other community groups benefit in improved service competence and cooperative relationships between healthcare providers and faith-based institutions.